The Effect of Compulsory Schooling Expansion on Mothers’ Attitudes Toward Domestic Violence in Turkey - Gulesci, Selim; Meyersson, Erik; Trommlerová, Sofia K. (Published by Oxford University Press on behalf of the World Bank, 2021)
An extensive literature examines the intergenerational spillover effects of education, but evidence on the causal effects of children's education on their parents’ outcomes is scarce. This paper estimates the spillover effects of children's schooling on their mothers’ attitudes toward domestic violence in Turkey. To identify the causal effect of children's schooling, we take advantage of a reform that took place in Turkey in 1997 and expanded compulsory schooling from five to eight years. Using a regression discontinuity design based on monthly birth cohorts and data from the 2008 and 2013 waves of the Turkey Demographic and Health Surveys, this paper shows that mothers whose eldest daughters were exposed to higher compulsory schooling are by 12 percentage points less likely to find domestic violence justifiable, which represents a decrease by 43 percent. We find no similar effect for boys’ schooling. Our findings demonstrate that children's schooling can have impacts on their parents’ attitudes, and such effects are likely to vary by the gender of the child.